Permissible technological limitations of quadrupole lenses used in parameter multiplets for ion microprobe forming - Melnik, K.I.; Ponomarev, A.G. (Вопросы атомной науки и техники, 2003)
Parasitic components of lens field are ones of the main parameters that determine spatial resolution of the MeV energy ion microprobe based on parameter multiplet of the magnetic quadrupole lenses. The parameter set of probe-forming systems was examined, the maximum permissible parasitic components of the lens field were computed, technological limitations on pole tips positioning accuracy were determined such that aberrations caused by them did not result in substantial beam degradation. Influence of the field parasitic components on ion-optical properties of multiplets was estimated, and computation technique was presented.